Myeloid-derived suppressor cells in cancer and cancer therapy - Lasser, Samantha; Özbay Kurt, Feyza Gül; Arkhypov, Ihor; Utikal, Jochen; Umansky, Viktor (Nature reviews. Clinical oncology, 2024)
Anticancer agents continue to dominate the list of newly approved drugs, approximately half of which are immunotherapies. This trend illustrates the considerable promise of cancer treatments that modulate the immune system. However, the immune system is complex and dynamic, and can have both tumour-suppressive and tumour-promoting effects. Understanding the full range of immune modulation in cancer is crucial to identifying more effective treatment strategies. Myeloid-derived suppressor cells (MDSCs) are a heterogeneous population of myeloid cells that develop in association with chronic inflammation, which is a hallmark of cancer. Indeed, MDSCs accumulate in the tumour microenvironment, where they strongly inhibit anticancer functions of T cells and natural killer cells and exert a variety of other tumour-promoting effects. Emerging evidence indicates that MDSCs also contribute to resistance to cancer treatments, particularly immunotherapies. Conversely, treatment approaches designed to eliminate cancer cells can have important additional effects on MDSC function, which can be either positive or negative. In this Review, we discuss the interplay between MDSCs and various other cell types found in tumours as well as the mechanisms by which MDSCs promote tumour progression. We also discuss the relevance and implications of MDSCs for cancer therapy.
Gesehen am 22.03.2024